LA GESTION ADMINISTRATIVA EN EL BANCO NACIONAL DE FOMENTO SUCURSAL BABAHOYO Y SU INCIDENCIA EN LA CALIDAD DE SERVICIO AL USUARIO. - OLGA MORENO MORA (2009)
ADMINISTRATIVE MANAGEMENT IN THE NATIONAL DEVELOPMENT BANK BABAHOYO BRANCH AND ITS IMPACT ON THE QUALITY OF SERVICE TO THE USER.